STRATEGI ADAPTIF MASYARAKAT SEKITAR HUTAN TERHADAP PERODE JEDA HUJAN DAN KEMARAU PANJANG - Hireng Ambaraji (Politeknik Sampit, 2023)
This research aims to identification local knowledge pesanggem as process to face from climate change disaster expecially rain lag and dry season. Pesanggem or intercropping farmers in RPH Menggoran forest area as population research. The sample is taken with snowball sampling technique and measured by slovin method, resulted as 93 pesanggem from 7 district in Bleberan village. The depth interview, questionnaire survey, field observation, and literature study are used to collect the research data. Data analysis will be done in descriptive and quantitative method. This research resulted that 1) the rain lag analysis in 2022 describes that the longest rain lag happened on May (12 days), in otherwise the longest dry season in 1984-2022 happened each years except in 1992, 1998, 2010, and 2022 ; 2) the adaptation strategy based on local knowledge is used in intercropping system with pranata mangsa calendar, the alley cropping and alternate cropping utilization, and solidarity stongest each farmer.